(3eNJUQ (B( (3cJGH (B) (3GdCdha hGdCOhGQs - (3GHi GdYHGS GdJfhNis; (3CHh eYTQ Gdadcj , CHh eYTQ LYaQ (B((3eMeO LYaQ(B) (3Hf eMeO Hf YeQ GdHdNj, CHh eYTQ GdHdNj,J (B272 (3g` s ((3MGLi Ydi GdQGRi s)
(3ChdgG (B:s
(3eNJUQ GdCSJGP GdCLd CHh GdYHGS GdJfhNi Cf Sfi GdYGde Ydi YOO CHQGL Gdadc hgj SJI TeSi hGdSfI GdhGMOI s
(3BNQgG (B:s
(3hEf cGf eYJOd GdSjQ ai GdMSGH hai GdYOO hGf cGf RGFOG Gh fGbUG efgG agPg CMhGd GdOdGdGJ GdXGgQI ef GdcJGH aGYdeg ced GdcJGH hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HChdgG Jedc SfI(B1249s
(3HgG fXGe GdJYbjHIs
(3cJHJ gPg GdfSNI fbdkG Yf fSNI LeYgG GHQGgje GdMGSH GdeGdci GdefUhQi GdfGUQi HeOjfI GdbGgQI SfI (B759(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdadcs